Penyuluhan Dan Pelatihan Peningkatan Soft Skill Bagi Remaja Untuk Memasuki Dunia Kerja - Listriyawati, Nyoman Ardiana; Rahmania, Andi Maulida; Wahyuni, Elli Setiyo; Prastiwi, Afita Dewi (Journal Of Human And Education (JAHE), 2025)
Adolesencents aged 18 and above in Keputih Timur Baru Urban Village Surabaya face challenges in the form of negative environmental exposure, lack of motivation to study, and lack of soft skills to prepare for entering the world of work. These factors include peer influence, social pressure, lack of family support, as well as educational conditions and technological literacy. Based on the situation analysis, it is deemed necessary to design a counselling and training program to improve the environmental exposure and prepare youth to enter the working evironmental. This community service focuses on increasing learning motivation in a supportive atmosphere for learning motivation in a supportive atmosphere for learning and developing adolesencets’ soft skill. This activity is conducted in a holistic approach through lectures, pre- and post-test, and English speaking practice. The result of this activity show an increase in soft skills and technological literacy of the participants in using English in oral and written communication.